Il simbolo della finestra nel Melkij Bes di F. Sologub (Altre Modernità, 2015)
This article explores the symbolic image of the “window” in Fyodor Sologub’s novel The Petty Demon (Melky bes), with a particular focus on the connections between literature, semiotics, and psychopathology. Windows can be thought of as thin and transparent frameworks which divide the external world (“the others”) from the internal one (“the self”), but, at the same time, they allow interactions between the two as well. Peaceful interactions are seldom contemplated; in most cases, the individual ego clashes with the collectivity. This is what happens in Sologub’s Petty Demon. Here, windows represent the struggle of the novel’s anti-hero Peredonov against the world; they stand as a symbol of his alienation from Russian society and life. Windows appear several times in the novel to signify Peredonov’s troublesome relationship with other people. In particular, broken windows and glasses suggest a growing gap between “the self” and “the others”, Peredonov and reality. Imagery drawn from the visual field helps the author to describe the protagonist’s fall into madness. On one hand, Peredonov sees the world through his paranoid eyes, and considers “the others” as a threat to his own identity. Even though, on the other hand, it is Peredonov himself, who suffering from persecution mania, fears that he is spied on by enemies. At the end, alterity will triumph over him. Thus, the novel also portrays Peredonov’s tragedy: the loss of his own “self”.